PENGARUH LAMA WAKTU PENGHITUNGAN STRAW DAN POSISI JARAK STRAW DIATAS PERMUKAAN NITROGEN CAIR TERHADAP MOTILITAS DAN VIABILITAS SEMEN BEKU SAPI MADURA POST THAWING - Ardiana, Lutfi; Hardijanto, Hardijanto; Damayanti, Ratna; Sardjito, Trilas; Mustofa, Imam; Utomo, Budi (Universitas Airlangga, 2018)
Aims of this research was to determine the effect of the duration of straw count and the position of straw from liquid nitrogen surface to the motility and viability of post thawing frozen Madura cattle. This study used a sample derived from Madura cattle (Pasean OO 1220) from BBIB singosari as much as 54 straw divided into 9 treatments. P1 (1cm 10 sec), P2 (1cm 20 sec), P3 (1cm 40 sec), P4 (2cm 10 sec), P5 (2cm 20 sec), P6 (2cm 40 sec), P7 (3cm 10 sec), P8 (3cm 20 sec), P9 (3cm 40 sec) and repeated as much as 6 times then observed for motility and viability of post thawing spermatozoa. The data obtained were analyzed using SPSS 16.0. The results showed that the duration of straw count and the position of straw from liquid nitrogen significant (P<0,05) on post thawing motility. The position of straw from liquid nitrogen signifant (P<0,05) on post thawing viability. The conclusion of this research showed that 1 cm 40 sec give the higher post thawing motility.